LEGAL ANALYSIS OF THE EFFECTIVENESS OF LAW ENFORCEMENT AGAINST PERPETRATORS OF DATA FALSIFICATION IN PASSPORT PROCESSING (RESEARCH STUDY AT THE CLASS I SPECIAL IMMIGRATION OFFICE OF TPI BATAM) - Maichel Fernando; Lagat Parroha Patar Siadari; Bachtiar Simatupang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Data forgery in passport management is a form of crime that has serious implications for the integrity of the immigration system and national security. The Class I Special Immigration Office TPI Batam, as one of Indonesia’s international gateways, is highly vulnerable to identity abuse by individuals or organized networks.This study aims to analyze the legal regulations governing sanctions against data forgery offenders, assess the effectiveness of their implementation in the field, and identify obstacles as well as formulate solutions that immigration officials can undertake to address these issues. This study employs normative juridical and empirical juridical research methods, using statutory and sociological (socio-legal) approaches. Data were obtained through literature reviews of regulations such as Law Number 6 of 2011 on Immigration, Government Regulation Number 31 of 2013 and its amendments, as well as Minister of Law and Human Rights Regulation Number 8 of 2014 in conjunction with Minister of Law and Human Rights Regulation Number 18 of 2022, and combined with interview results and field observations involving officials and the community at the Batam Immigration Office. The research findings indicate that although legal norms regarding the enforcement against data forgery have been formally established, the effectiveness of their implementation is still hindered by internal factors such as limited human resources, technology, and officer competence, as well as external challenges such as increasingly complex crime modes and weak inter-agency coordination. Law enforcement has also not fully reflected substantive justice nor been responsive to the social dynamics of the community. Therefore, it is necessary to strengthen institutional capacity, integrate national data systems, and enhance public legal literacy as more effective preventive and repressive measures in the future